2019
DOI: 10.5644/ama2006-124.254
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Stress, Burnout Syndrome and the Most Important Causes of Working Stress Among Physicians in Primary Health Care – an Observational Study from Banja Luka, Bosnia and Herzegovina

Abstract: <p><strong>Objective. </strong>To investigate the level and causes of stress and the risk of onset of burnout syndrome among physicians employed at the Primary Health Care Centre, Banja Luka.</p><p><strong>Subjects and Methods. </strong>Between March 1, 2018, and May 31, 2018 all physicians from the Primary Health Care Centre, Banja Luka were offered the following questionnaires to fill in: a socio-demographic questionnaire, a questionnaire for self-assessment of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The main results of this study also indicated that primary healthcare workers who perceived a higher level of occupational stress, especially for hindrance stress, tended to develop subclinical depression symptoms. Similar to findings from other study, a high level of stress was associated with a high degree of emotional exhaustion as well as lack of personal accomplishment among physicians in primary health care (24). Meanwhile, higher level of perceived stress was significantly positively related to severe insomnia and depression among medical staff (25).…”
Section: Discussionsupporting
confidence: 84%
“…The main results of this study also indicated that primary healthcare workers who perceived a higher level of occupational stress, especially for hindrance stress, tended to develop subclinical depression symptoms. Similar to findings from other study, a high level of stress was associated with a high degree of emotional exhaustion as well as lack of personal accomplishment among physicians in primary health care (24). Meanwhile, higher level of perceived stress was significantly positively related to severe insomnia and depression among medical staff (25).…”
Section: Discussionsupporting
confidence: 84%
“…Burnout among BiH physicians was investigated before the pandemic among physicians in primary health care from Banja Luka. The study was based on the MBI, and 20.9% of respondents had a high level of emotional exhaustion, 43.2% had a high level of depersonalization ( 36 ), and emotional exhaustion and depersonalization were suggested to be the foundation of burnout ( 5 ). Another survey based on MBI, conducted among primary health care providers in the Sarajevo Canton, showed that 25.3% of HCWs experienced a high level of emotional exhaustion and 17.7% experienced depersonalization ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the year of publication, one article was published in 2003 15 , 2009 19 , 2010 23 , 2013 25 , 2015 17 and 2021 13 , while two in 2017 16,24 , 2018 18,20 , 2019 14,26 and 2022 21,22 . Brazil stood out with seven productions 13,16,17,20,22,25,26 .…”
Section: Resultsmentioning
confidence: 99%
“…Brazil stood out with seven productions 13,16,17,20,22,25,26 . The other articles were divided in this way: two carried out in Bosnia-Herzegovina 14,24 , two in China 15,18 , one in Mexico 19 , one in Singapore 21, and one concurrently in the United States, United Kingdom, and Germany 23 .…”
Section: Resultsmentioning
confidence: 99%